Awareness of COVID 19 vaccine in a Rural Area near Bangalore, Karnataka - Ramesh Masthi N R; Sowmyashree U (Medsci Publications, 2021)
Background: COVID 19 vaccines was launched as Phase I on 16TH January 2021 in India for Health workers. The study was conducted to assess the awareness and willingness to accept the COVID19 vaccine in a rural population. Method: A descriptive cross-sectional study in the rural area near Bangalore was conducted in January 2021. A total of 846 adult subjects were enrolled. Subjects were interviewed using a semi structured questionnaire about COVID 19 vaccine and willingness to get vaccinated. Results: Of 846 participants, minimum age of the respondent was 18 years and maximum was 90 years. 689 (81.4%) were literates and 157(18.6%) illiterates. Awareness about COVID 19 disease was 838 (99.1%). 710(83.9%) subjects were aware about vaccine. A total of 545(64.4%) were willing to take the vaccine and 50% informed will take the vaccine to prevent infection. Maximum fear was associated with side effects among 66.1% of the population. 37.1% would not like to vaccinate the family members mostly children and elderly. Conclusion: Awareness about COVID 19 vaccine was seen in more than two third of the subjects. However, vaccine acceptance was about 60% in the rural area. An effective BCC strategy to combat vaccine hesitancy is necessary for better coverage in subsequent vaccination drives.